Ghost-writing for Sara Allgood - Kelly, John (Open Book Publishers, 2016)
Ghost-writing for Sara Allgood was a task which intrigued and frustrated Yeats in almost equal measure (as, indeed, she herself often did). Maire nic Shiubhlaigh’s resignation from the Abbey Theatre Company in early January 1906 left the stage literally clear for Allgood to assume the role of undisputed Irish diva, and she enjoyed a commanding and growing reputation as an actress, not only in Dublin but also more widely in Ireland and Britain, and particularly in Belfast, London, Oxford, and Manchester....